ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PENGGUNAAN SISTEM LISTRIK PRABAYAR SEKTOR RUMAH TANGGA DI WILAYAH SEMARANG SELATAN - Puji Wibowo; Nawazirul Lubis; Naili Farida (Jurnal Ilmu Administrasi Bisnis, 2013)
This study aims to determine the most dominating factor between psychological factors, social factors, and personal factors / personal in influencing decisions PLN use prepaid electricity system and also to know the perceptions of consumers about prepaid electricity system. The research was conducted through descriptive research. The number of samples in this study amounted to 94 respondents were taken by purposive sampling technique. Measurement scale with a Likert scale. Data collection by interview using a guiding question and questionnaires. Analysis of the test data using factor analysis with SPSS 16.0.Statistical calculations it can be concluded that the personal factor variables / personal (X3) dominance is very strong, with the acquisition of a value of 0766. Psychological factor variable (X1) strong dominance, with the acquisition value of 0.692. Variable social factors (X2) dominance is strong enough, the acquisition value of 0.515.The conclusion is that the respondents felt a strong psychological factor in the decision category of prepaid electricity use, social factors in the category is strong enough for the decision of prepaid electricity usage, and personal factors / personal in a very strong category for decisions using prepaid electricity system. PT PLN (Persero) should consider social factors in order to attract more consumers to use or switch to a prepaid electricity system by way of more intensive socialization of the prepaid electricity. It is also recommended to management to improve the ease of the procedure can reload prepaid electricity anytime and anywhere. Improve the management of services to suit customer needs, such as providing complete information on the use of prepaid electricity system and provide ease of provision of purchase of prepaid electricity pulses.